The Structure and Semantics Of The Linguocultural Field Of "Sacrifice" In The Uzbek Language - Shokhsanam, Mamatqulova (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
The article analyzes the structure and semantics of the linguistic and cultural field of the concept of "Devotion", and describes the units expressing the values ​​of devotion in the Uzbek and English languages.